To systematics of the mite genus Hoplocheylus (Acariformes: Tarsocheylidae) - Khaustov, Alexander A. (Zootaxa, 2015)
A new species of the genus Hoplocheylus Atyeo and Baker, 1964 (Acariformes: Heterostigmatina: Tarsocheylidae), H. magnificus sp. nov. is described from the nest of the ant Formica rufa Linnaeus (Hymenoptera: Formicidae) from Kurgan Province, Western Siberia, Russia. A poorly-known species Hoplocheylus sogdianicus Barilo and Sharipov, 1987 is redescribed from the holotype. A key to species of the genus Hoplocheylus is provided.